Economic Policy Uncertainty Spillovers in Booms and Busts - Giovanni Caggiano; Efrem Castelnuovo; Juan Manuel Figueres (Center for Economic Studies and ifo Institute (CESifo), 2018)
We estimate a nonlinear VAR to quantify the impact of economic policy uncertainty shocks originating in the US on the Canadian unemployment rate in booms and busts. We find strong evidence in favor of asymmetric spillover effects. Unemployment in Canada is shown to react to uncertainty shocks in economic busts only. Such shocks explain about 13% of the variance of the 2-year ahead forecast error of the Canadian unemployment rate in periods of slack vs. just 2% during economic booms. Counterfactual simulations lead to the identification of a novel “economic policy uncertainty spillovers channel”. According to this channel, jumps in US uncertainty foster economic policy uncertainty in Canada in the first place and, because of the latter, lead to a temporary increase in the Canadian unemployment rate. Evidence of asymmetric spillover effects due to US EPU shocks are also found for the UK economy. This evidence, which refers to a large economy having a low trade intensity with the US, supports our view that a channel other than trade could be behind our empirical results.
Keywords: C32; E32; E52; 330; economic policy uncertainty shocks; spillover effects; unemployment dynamics; smooth transition vector autoregressions; recessions